Maintaining and Shaping Ecological Citizenship of Indigenous Balinese Through Saput Poleng - I Nengah Agus Tripayana; Prayoga Bestari; Elly Malihah; Syaifullah Syaifullah (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
This research was motivated by various environmental damages that occurred around Seraya village, Karangasem, Bali. Many factors of damage are caused by human actions such as illegal logging of forests and trees, indifference of the community to their dirty environment, and so on. This study aims to examine the use and impact of saput poleng on environmental sustainability and the effectiveness of saput poleng in the formation of ecological citizenship in Balinese indigenous communities. This type of research uses a qualitative approach with ethnographic methods. Data analysis uses data reduction, data analysis and verification or conclusion. Environmental conservation efforts by using saput poleng on certain trees create a mystical impression and can prevent intentions and behaviors to protect the existence of trees and support beautiful and sustainable environmental conditions. The results showed that the use of saput poleng on trees is not a fad, but has philosophical and religious values that are highly adhered to by the local community. The habit of pairing saput poleng is able to preserve trees, the environment and is very effective in forming ecological citizenship.Keywords: Ecological citizenship, indigenous Balinese, saput polengÂ